Ranges of Vigor Based on the Electrical Conductivity Test in Dehulled Sunflower Seeds - Szemruch, Cyntia Lorena; del Longo, Olga Teresita; Ferrari, Liliana; Renteria, S.J.; Murcia, Marcos German; Cantamutto, Miguel Angel; Rondanini, Deborah Paola (Academic Journals, 2019)
Electrical Conductivity (EC) is a promising vigor test since it produces fast laboratory results. In sunflower, the leakage of electrolytes from the pericarp may interfere with exudates from embryo tissues. The aims of this work were (1) To determine the utility of the EC test using dehulled (without pericap) sunflower seeds to evaluate the vigor in different genotypes, exposed to contrasting seed filling period and storage conditions, (2) To explore the relationship between EC and germination values near post harvest and across storage period and (3) To propose ranges of vigor through EC, so as to categorize sunflower seeds lots. Seeds of commercial hybrids differentiated by acid composition (high and standard oleic acid), exploring contrasting seed filling period and storage conditions, were evaluated by EC, Tetrazolium (TZ-V) and Germination (G), near post harvest time and during storage period (1, 5, 9, 13 and 19 months). An independent set of 18 genotypes, stored during 1-108 months, were also analyzed for EC and G. Electric conductivity in dehulled seeds was effective to identify vigor differences of genotypes in different seed filling period and storage conditions. A general relationship between the loss of germination and vigor was established for sunflower. The ranges of vigor based on EC proposed for sunflower seeds classification were <70 μs cm–1 g–1 for high, 70-110 μs cm–1 g–1 for intermediate and >110 μs cm–1 g–1 for low vigor levels. It is the first report based on EC ranges to categorize the seed vigor of sunflower seeds lots.